Partition of spaces based algorithm for reduction of real power loss - Kanagasabai Lenin (Institute of Advanced Engineering and Science, 2020)
In this work partition of spaces algorithm is proposed to solve optimal reactive power problem. In this algorithm, for finding the finest outcome based on the concentration of elevated quality and capable points in specific area is considered. State space area are identified and divided into subspaces iteratively and search has been made more comprehensively. Performance of the proposed partition of spaces algorithm is evaluated in standard IEEE 118,300 bus systems and simulated outcome gives better results. Real power loss has been considerably reduced.